ANALISIS PERSEPSI DOSEN TERHADAP SIKAP PENGGUNAAN TEKNOLOGI SISTEM INFORMASI E-LEARNING DENGAN BLOG - Erfianti, Silvia Dwi (Jurnal Ilmiah Mahasiswa FEB, 2016)
The purpose of this study is to examine the factors that influence the attitude toward the use of e-learning with blog using the Innovation Diffusion Theory (IDT) proposed by Rogers (1964). This research was conducted at the Faculty of Economics and Business at the University in East Java Region with 80 lecturers as respondents. This research uses multiple linear regression analysis with SPSS 17 software to examine the research data. The results of this analysis showed that simultaneously, variable of relative advantage, compability, triability, and observability significantly influence the attitude toward using e-learning with blog. According to the t-test, variable of relative advantage, compability and triability significantly influence the attitude toward using e- learning with blog. Otherwise, the variable of observability has not significantly influence to the attitude toward using  e-learning with blog. It could be conclude that the attitude toward using blog as e-learning media is influenced by variable of relative advantage, compatibility and triability. The implications of this study are relevant to the education sector, mainly online learning, particularly the institutions, in order to pay attention to the relative advantages, compability, and triability in implementing and developing e-learning with blog.   Keywords: Relative   advantage,   compability,   triability,   observability,   attitude, information system technology (e-learning), blog.